On the mend of bryophyte conservation in Spain: preparing a proposal for the inclusion of bryophytes in national species protection catalogues - Albertos, Belén; Garilleti, Ricardo; Heras, Patxi; Infante, Marta (Mediterranean Botany, 2018)
The Spanish bryoflora contains 1291 taxa, 272 of them included in the Spanish Red List under any threat category. Although bryophytes show a low rate of endemicity compared to vascular flora, Spanish administration’s responsibility for the conservation of these plants is very high, since the country has 63 exclusive or rare species on a European or world scale. However, the representation of this group of plants in the Spanish legislation on species conservation is merely anecdotal. Royal Decree 139/2011 of 4 February develops a list of wild protected species (LESRPE and CEEA, Spanish abbreviations) and includes only 10 species of bryophytes, all of them from the Directive Habitats and the Bern Convention. The legal protection of endangered species of bryophytes is needed, not only to ensure the integrity of the most sensitive bryophyte populations, but also because it will result in the overall protection of their habitats and other species that coexist with them. Their inclusion in LESRPE and CEEA will allow a periodical monitoring of the species and a better assessment of the success or failure of commonly used management measures. The criteria for the incorporation of species into national protection catalogues are rather restrictive and inclusion of species without specific studies is not easy. During the work developed for the Atlas and Red Data Book of the threatened bryophytes of Spain, valuable information was obtained in this sense, although it covered only a fraction of the total number of species on the Red List (74 species were evaluated). Based on the available information, a list of species has been drawn to elaborate a proposal that should be raised to the Spanish Ministry of Agriculture and Fisheries, Food and the Environment, which would imply a qualitative leap in the level of protection of this neglected group of plants and a new impetus to the necessary work started at the first phase of the Bryophyte Atlas.